The effect of butt joint on the structural behaviour of PSSDB wall panel / Siti Hawa Hamzah ... [et al.] - Hamzah, Siti Hawa; Yong, Chua Bon; Saari @ Ash’ari, Nadiah; Marwi, Mat Som (Institute of Research, Development and Commercialisation (IRDC), 2007)
An experimental investigation was carried out to determine the effect of butt joint on the structural behaviour of profiled steel sheet dry board (PSSDB) load bearing wall with window opening. The samples tested were three (3) PSSDB walls with window opening and butt joint in the dry boards, and three (3) PSSDB walls with window opening but without butt joint in the dry boards. The samples were subjected to axial compressive load and comparisons were made between the two sets of samples. The average value of the ultimate load capacity for PSSDB load bearing wall with butt joint was found to be 286 kN, while that for the samples of PSSDB load bearing wall without butt joint was 260 kN. The average maximum lateral deflection values for both types of PSSDB walls were 8.9 mm and 13 mm respectively. Significant difference due to butt joint in dry board was seen in the reduced number of cracks by about 33 % in comparison to that without butt joint.